Editorial - Neves, Pedro Soares (Architecture Image Studies, 2024)
The fields of architecture, design, and art are dynamic, constantly evolving to reflect the complexities of contemporary life. This issue presents a rich collection of research that explores these intersections through a variety of lenses, from philosophical inquiries into design education to the practical implications of planting design in modern interiors. The papers included here, authored by experts from diverse geographical and academic backgrounds, provide critical insights into how these disciplines inform and transform the spaces we inhabit.